1996
DOI: 10.1002/(sici)1096-911x(199608)27:2<114::aid-mpo8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antileukemic activity in vitro of dexamethasone and prednisolone in childhood acute lymphoblastic leukemia

Abstract: It is generally assumed that prednisolone (PRD) and dexamethasone (DXM) have equal glucocorticoid activity if PRD is given at sev enfold higher doses. Resuits of clinical studies of childhood acute lymphoblastic leukemia (ALL) suggested that DXM is more potent relative to PRD than assumed. The purpose of this study was to determine the relative antileukemic activ ity of PRD phosphate and DXM phosphate in 133 untreated childhood ALL samples in vitro, using the 3-(4,5-dimethylthiazol-2~y!)-2,5~diphenyltetrazoliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 46 publications
1
39
2
1
Order By: Relevance
“…Our analysis suggests that this heterogeneity is largely related to different PRED/DEX dose ratios applied in the different trials, with greater efficacy with larger relative DEX dosing, indicating that the presumed equivalent anti-leukemic activity for PRED/ DEX is not a 6:1-7:1 dose ratio, but is higher, as some in vitro experiments suggest. 38 Although our study is able to provide further information in regard to relative corticosteroid doses, the impact of absolute doses on our findings remains unknown. Meta-regression would have been an optimal approach to further explore a dose-effect function of PRED and DEX; however, too few studies were available to consider such an analysis.…”
Section: Discussionmentioning
confidence: 87%
“…Our analysis suggests that this heterogeneity is largely related to different PRED/DEX dose ratios applied in the different trials, with greater efficacy with larger relative DEX dosing, indicating that the presumed equivalent anti-leukemic activity for PRED/ DEX is not a 6:1-7:1 dose ratio, but is higher, as some in vitro experiments suggest. 38 Although our study is able to provide further information in regard to relative corticosteroid doses, the impact of absolute doses on our findings remains unknown. Meta-regression would have been an optimal approach to further explore a dose-effect function of PRED and DEX; however, too few studies were available to consider such an analysis.…”
Section: Discussionmentioning
confidence: 87%
“…Two of the most important glucocorticoids used for treating childhood ALL are PRED and DEX. Although DEX consistently shows higher antileukemic activity both in vitro and in vivo 4,[15][16][17] , PRED is used in most chemotherapy protocols due to its better toxicity profile. DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 . Several studies, including ours [4][5][6]16 , have shown that leukemia cells from different patients can exhibit different responses to PRED and DEX. However, the development of personalized glucocorticoid therapies based on the in vitro response of leukemia cells to individual glucocorticoids is clinically challenging because of time constrains (MTT assay would delay onset of therapy for minimum 4 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Dexamethasone is 6.5 times more potent than prednisolone as measured by conventional glucocorticoid activity, but it shows a 16-fold gain in potency against lymphoblasts in vitro, suggesting that it might be a more active corticosteroid in the treatment of ALL. 6,7 The better penetration in the central nervous system (CNS) 8 and the enhanced lymphoblastic cytotoxicity might explain the lower bone marrow relapse rate, the lower CNS relapse rate and the advantage in event-free survival recorded in children receiving dexamethasone . [9][10][11] However, attempts to increase the antileukemic effect of dexamethasone by increasing its dose have been associated with increased toxicity and early deaths, mostly due to severe infections.…”
Section: Introductionmentioning
confidence: 99%